Measuring Empowerment: the Women’s Empowerment in Agriculture Index (WEAI) and project-level Women’s Empowerment in Agriculture Index (pro-WEAI) - Meinzen-Dick, Ruth S.; Quisumbing, Agnes R.; Malapit, Hazel J.; Johnson, Nancy L. (2018)
As part of the IFPRI Egypt Seminar in partnership with UN Women: “Women Empowerment for Revitalizing Rural Areas in Egypt”